PATOFISIOLOGI DAN NEUROBIOLOGI FIBROMIALGIA DENGAN DEPRESI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
Fibromialgia is a chronic pain where the causes have not been known, with the sign of spread out musculoskeletal pain, rigidity,.and spread out fatigue. The complaint of pain is usually felt for more than three months. frequently being followed with additional symptom of depression. Fibromialgia Is a complex disorder. So far, not all parts of Fibromialgia are understood, though the main component is already,known. Flbromialgia is illustrated as disorder of central nervous system, where an Increase of central sensitization happened, connected with a complex role of genetic predisposition, stressor accumulation, and dlsregulatlon of normal respond to pain. Depression Is 8 multiple symptom with the main illustration is mood disorder influencing to cognitive, ' psychomotor and psychosocial presentation, accompanied with difficulty in personal relationship. or can be seen as two different things I.e., 1) As a symptom or situation of feeling sad, or hopeless. and. 2) As a syndrome or a ,disease where there Is a depressed feeling accompanied with the decrease of physical and mentSl activities. Understanding about, patophyslologlcal and neurobiological relationship of the two diseases Is so far still in progress and under dispute. Flbromlalgla and depression are predicted having resemblance In biochemical milieu of neurotransmitter such as serotonin, epinephrine. corticotrophin releasing hormone (CRH), and, dopamine. Some researches have important clinical and theoretical impacts. where there Is 8 possibility that flbromialgla and depression have a patophysiologic and neurobiologicalrelationship. ' Keywords:flbromyalgla,depression,pathophysiology, neurobiology.